Lateral epicondylitis treatment: international survey of surgeons' preferences and literature review. Issue 11 (16th July 2014) - Amar, E.; Chechik, O.; Khashan, M.; Lador, R.; Rath, E.
Summary: Background: Lateral epicondylitis (LE) is a common cause of elbow pain. Despite a relatively high prevalence and morbidity, there is still no single effective ('gold standard') treatment for LE. We hypothesised that a surgeon's experience, country of origin and area of expertise would influence choices concerning patient management. The purpose of this survey was to describe the current trends and common practices in treating LE worldwide. Material and methods: A total of 291 orthopaedic surgeons of 12 subspecialties from 57 countries were surveyed on their choice of LE treatment modalities. Their preferences were analysed according to country of origin, field of expertise and seniority. The results were compared with current published level‐1 evidence. Results: The most popular modalities of treatment among all of the surveyed orthopaedic surgeons were non‐steroidal anti‐inflammatory drugs (NSAIDs) and corticosteroid (CS) injection (38% of recommendations each). The most popular Modalities of treatment among the hand surgeons was NSAIDs (48%) and CS injection (30%). There was no significant difference in recommendations based on geography, seniority or specialisation (i.e., hand surgeons among others). Conclusions: Neither geography, seniority nor medical specialty affects surgeons' preferences in the treatment of LE. There appears to be little correlation between scientific evidence and therapeutic choices for managing LE. Level of evidence: Level V, Study.